Comprehensive Atlas of Wheat (Triticum aestivum L.) AUXIN RESPONSE FACTOR Expression During Male Reproductive Development and Abiotic Stress - Xu, Lei; Wang, Dezhou; Liu, Shan; Fang, Zhaofeng; Su, Shichao; Guo, Chunman; Zhao, Changping; Tang, Yimiao (Frontiers in Plant Science, 2020)
AUXIN RESPONSE FACTOR (ARF) proteins regulate a wide range of signaling pathways, from general plant growth to abiotic stress responses. Here, we performed a genome-wide survey in wheat (Triticum aestivum) and identified 69 TaARF members that formed 24 homoeologous groups. Phylogenetic analysis clustered TaARF genes into three clades, similar to ARF genes in Arabidopsis (Arabidopsis thaliana) and rice (Oryza sativa). Structural characterization suggested that ARF gene structure and domain composition are well conserved between plant species. Expression profiling revealed diverse patterns of TaARF transcript levels across a range of developmental stages, tissues, and abiotic stresses. A number of TaARF genes shared similar expression patterns and were preferentially expressed in anthers. Moreover, our systematic analysis identiﬁed three anther-specific TaARF genes (TaARF8, TaARF9, and TaARF21) whose expression was signiﬁcantly altered by cold stress in thermosensitive genic male-sterile (TGMS) wheat; these TaARF genes are candidates to participate in the cold-induced male sterility pathway, and offer potential applications in TGMS wheat breeding and hybrid seed production. Moreover, we identified putative functions for a set of TaARFs involved in responses to abscisic acid and abiotic stress. Overall, this study characterized the wheat ARF gene family and generated several hypotheses for future investigation of ARF function during anther development and abiotic stress.